DISTRIBUSI VERTIKAL KUMBANG TINJA SCARABAEIDAE (COLEOPTERA: SCARABAEIDAE) DI HUTAN TROPIS BASAH PEGUNUNGAN TAMAN NASIONAL GEDE-PANGRANGO, JAWA BARAT - Sih Kahono; Lilik Kundarsetiadi (BERITA BIOLOGI, 2007)
Vertical distributions of scarabaeids dung beetles (Coleoptera: Scarabaeidae) were studied in a tropical mountaineous rainforest of Gede-Pangrango National Park using human dung traps. Samples were collected at four different altitudes of 500-1000m, 1001-1500, 1501-2000 and 2001-2500m of five different collection sites (Cibodas, Selabintana, Situ Gunung, Bodogol, and Gunung Putri). As many as 1052 individuals of 28 species of scarabaeid dung beetles that belonging to five genera were collected.Onthophagus was the most diverse group, which consists of 21 species (75% of collected species) and followed by Copris with 3 species (10.7%), Paragymnopleurus with 2 species (7.1%), Catharsius with 1 species (3.6%), and Phacosoma with 1 species (3.6%). The Shanon-Winner index of diversity and evenness gradually declined with the increase of altitudes. The different of environment conditions on each altitude might affect to the diversity, abundance, and distribution of dung beetles. The diversity of dung beetles at the interval of 1001-1500m and 1501-2000m were not so high but abundance and similarity were high. Diversity index, evenness, abundance, and species similarity of dung beetles at the interval of 2001-2500m was low because of unfavorable habitat. Although the diversity of dung beetles at the interval 500-1000m was the highest, however abundance and similarity index were relatively low. Analyze of diversity, abundance, evenness, and similarity indexes of dung beetles on each of the different altitudes and environment conditions were discussed in this paper.